INTEGRATIVE RESEARCH REVIEW APPLIED TO NURSING - Arlete Regina Roman; Maria Romana Friedlander (Universidade Federal do Paraná, 1998)
The Integrative Research Review or Integrative Research is defined as a method that intends to systematize results attained in investigations concerning a well defined question. It discloses its advantages to the caring and teaching áreas considering the rapid knowledge amplification and easy access to information. Finally, it describes the main procedures needed for its development in consideration with the different stages of methodological process. In order to facilitate its comprehension it presents a synthetical picture about the method's characteristics based in Cooper's studies.